Para-aramid paper and preparation method thereof

By preparing nanofiber dispersion liquid and combining wet molding and other processes, the problem of para-aramid paper being difficult to disperse evenly in water is solved, and the high uniformity and mechanical properties are improved, avoiding the high cost and performance impact of the dispersant.

CN119593243AActive Publication Date: 2025-03-11YANTAI METASTAR SPECIAL PAPER
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411919353.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-11
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The existing para-aramid paper is difficult to disperse evenly in water, resulting in poor uniformity, high porosity and insufficient mechanical properties. The method of using dispersants is expensive and affects dielectric properties and temperature resistance.

Method used

By preparing nanofiber dispersion liquid, para-aramid chopped fibers and meta-aramid precipitation fibers are dispersed and stirred to form a stable dispersion liquid. Para-aramid paper with high uniformity and excellent mechanical properties is obtained through wet molding, pressing, drying and hot pressing processes.

Benefits of technology

The high uniformity and mechanical properties of para-aramid paper are achieved, which reduces the risk of porosity and glue transmissibility, and avoids the high cost and performance impacts caused by the use of dispersants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of synthetic fiber paper manufacturing, in particular to para-aramid paper and a preparation method thereof, and belongs to the technical field of synthetic fiber paper manufacturing. The preparation method comprises the following steps: adding para-aramid chopped fibers and potassium hydroxide into dimethyl sulfoxide, then adding water, and stirring and dispersing to obtain nanofiber dispersion liquid; adding para-aramid chopped fibers into the nanofiber dispersion liquid for defibering, and uniformly mixing to obtain para-aramid chopped fiber dispersion liquid; the preparation method comprises the following steps: continuously and stably adding a meta-aramid polymer liquid, a nanofiber dispersion liquid and a precipitation agent into precipitation equipment, carrying out high-speed shearing to obtain a fibrid, then carrying out cooling molding in a water washing pool, and carrying out multi-stage water washing to obtain the meta-aramid fibrid, and carrying out wet papermaking on the para-aramid chopped fiber dispersion liquid and meta-aramid fibrid to obtain the para-aramid paper. The para-aramid paper is higher in mechanical property, good in uniformity and high in density, and the glue penetration risk in the process of preparing honeycombs from the para-aramid paper is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a para-aramid paper and a preparation method thereof, belonging to the technical field of synthetic fiber paper manufacturing. Background Art

[0002] Para-aramid paper, which is made from para-aramid fiber through a papermaking process, has the advantages of light weight, high strength, excellent dielectric properties, solvent properties and thermal dimensional stability. It can be used as a structural material, insulating material, wave-transparent and filter material, and is widely used in aerospace, military equipment, electronics and electrical appliances and other industries.

[0003] However, since the molecular chain of poly(p-phenylene terephthalamide) (PPTA) constituting para-aramid is a rigid structure, the fiber surface is hydrophobic, smooth and has high inertness, which leads to the easy agglomeration of para-aramid fiber and its differentiated products (short fibers, pulp and precipitated fibers) in water, making it difficult to disperse evenly, reducing the uniformity of para-aramid paper, and the porosity of some positions is large, and there will be a phenomenon of glue penetration when preparing honeycombs. In addition, the smooth and inert surface of para-aramid fiber makes the bonding force between fibers very weak, and the advantage of excellent mechanical properties of para-aramid cannot be brought into play. In Chinese patent application CN1884692A, a dispersant is used to disperse the fibers, which greatly improves the uniformity of paper, thereby improving the performance of paper strength, etc. Chinese patent application CN1710196A adopts a dispersing aid to disperse para-aramid short-cut fibers and pulp fibers to prepare a mixed slurry, and then obtains fiber paper by wet molding, squeezing, and drying, and then the obtained fiber paper is evenly impregnated with a para-aramid solution, and then subjected to hot pressing or cold pressing treatment, solidified liquid molding, washing away the solvent, dehydration, squeezing, and drying to obtain the final full-para-aramid paper. Although the above patents have improved paper uniformity and mechanical properties, the paper uniformity and mechanical properties such as paper tensile strength and tear resistance still need to be further improved. At the same time, the method of using a dispersant to disperse the fibers is expensive, and the dispersant is added during the preparation process, and the sewage treatment procedure is complicated. In addition, the presence of the dispersant affects the temperature resistance of the paper and the dielectric properties of the paper.

[0004] Therefore, it is of great value to develop a para-aramid paper with high uniformity and excellent mechanical properties. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a para-aramid paper and a preparation method thereof. The para-aramid paper has higher mechanical properties, good uniformity and high density, and reduces the risk of glue penetration in the process of preparing honeycombs using the para-aramid paper.

[0006] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing para-aramid paper, the preparation method comprising: S1. Preparation of nanofiber dispersion: Adding para-aramid chopped fibers and potassium hydroxide into dimethyl sulfoxide, then adding water, stirring and dispersing, to obtain the nanofiber dispersion; S2. Preparation of para-aramid chopped fiber dispersion and meta-aramid fiber precipitation: Adding the para-aramid chopped fibers into the nanofiber dispersion to disperse and mix evenly to obtain the para-aramid chopped fibers dispersion; The meta-aramid polymer solution, nanofiber dispersion solution and precipitating agent are continuously and stably added into the precipitation device, and the precipitated fibers are obtained by high-speed shearing, and then cooled and formed in a washing tank, and multi-stage washing is performed to obtain the meta-aramid precipitated fibers; S3. Preparation of para-aramid paper: The para-aramid short fiber dispersion and meta-aramid fiber precipitation are subjected to delamination, stirring, wet forming, pressing, drying and hot pressing to obtain the para-aramid paper.

[0007] Furthermore, in step S1, the stirring time is 4 to 24 hours, and the storage temperature of the nanofiber dispersion is 15-25°C.

[0008] Furthermore, in step S1, the weight ratio of the para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is (0.05-3): (80-100): (0.01-0.08): (0.15-4).

[0009] Furthermore, in step S2, when preparing the para-aramid chopped fiber dispersion, the deflaking time is 5 to 15 minutes; and the mass concentration of the para-aramid chopped fibers in the para-aramid chopped fiber dispersion is 0.05% to 1%.

[0010] Furthermore, in step S2, when preparing the meta-aramid fiber, the meta-aramid polymer solution has a temperature of 35 to 50° C., a solid content of 8% to 15%, and a viscosity of 100 to 450 Po at 25° C.; When preparing the meta-aramid fiber precipitation, the weight ratio of the nanofiber dispersion liquid, the precipitating agent and the meta-aramid polymer liquid is (5-20): (5-12): (80-100).

[0011] Furthermore, in step S2, when preparing the meta-aramid fibrid, the high-speed shearing speed is 3500 to 6000 rpm, and the high-speed shearing time is 40 to 90 s.

[0012] Furthermore, in step S2, when preparing the meta-aramid fiber, the precipitating agent is prepared by mixing and compounding the following materials in parts by weight: 5 to 18 parts of chloride salt, 40 to 50 parts of water, and 40 to 50 parts of N,N-dimethylacetamide; The chloride salt is at least one of lithium chloride, calcium chloride and magnesium chloride.

[0013] Furthermore, in step S3, the weight ratio of the para-aramid chopped fiber dispersion and the meta-aramid fibrid is (8-2):(2-8), and the total weight ratio of the para-aramid chopped fiber dispersion and the meta-aramid fibrid is 10 parts.

[0014] Furthermore, in step S3, the hot pressing conditions are: temperature 180-220° C., vehicle speed 5-20 m / min, and pressure 100-300 N / mm.

[0015] The invention also discloses a para-aramid paper, and the para-aramid paper is prepared according to the preparation method of the invention.

[0016] The beneficial effects of the present invention are: 1. The nanofiber dispersion is an anionic system, which is very stable and has a certain viscosity. The system can disperse the para-aramid chopped fibers and maintain a certain steady state. Without the addition of a dispersant, the para-aramid chopped fibers can be well dispersed and not easily flocculated. This makes the para-aramid paper have higher uniformity and better mechanical properties.

[0017] 2. During the precipitation of the nanofiber dispersion in water, para-aramid nanofibers are attached to the surface of the para-aramid chopped fibers, making the smooth surface of the para-aramid chopped fibers rough. Therefore, the interfacial bonding strength between the para-aramid chopped fibers and the para-aramid chopped fibers, and between the para-aramid chopped fibers and the meta-aramid precipitated fibers is enhanced, and the inter-fiber bonding force is greater, so that the stress is better transferred and the bonding force of the aramid paper is improved. Moreover, the roughness is not obtained by sacrificing the original performance of the para-aramid fibers. At the same time, the method can significantly reduce the porosity of the para-aramid paper, and then improve the uniformity of the para-aramid paper, and obtain the para-aramid paper with good mechanical properties. The meta-aramid precipitated surface prepared by the present invention has more tiny wrinkles, which can be more strongly bonded to other fibers and also improve the bonding force of the aramid paper.

[0018] 3. The introduction of para-aramid nanofiber dispersion during the preparation of meta-aramid precipitation reduces the crystallinity of meta-aramid precipitation fibers, making them easier to melt during hot pressing, with stronger bonding between fibers and smoother surfaces. At the same time, it also increases the density of para-aramid paper, reduces the porosity of para-aramid paper, and greatly reduces the risk of glue penetration during the preparation of honeycombs using para-aramid paper.

[0019] 4. Compared with conventional meta-aramid fiber precipitation, the meta-aramid fiber precipitation in the present invention is a low-crystallinity meta-aramid fiber precipitation, which can achieve good melting and bonding at a relatively low hot pressing temperature, and can significantly reduce production energy consumption while maintaining good mechanical properties of aramid paper. The preparation process of the present invention is simple, low in energy consumption, and easy to control. DETAILED DESCRIPTION

[0020] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0022] A method for preparing para-aramid paper, the preparation method comprising: S1. Preparation of nanofiber dispersion: Para-aramid chopped fibers and potassium hydroxide are added to dimethyl sulfoxide, followed by water and mechanical stirring to obtain a stable nanofiber dispersion; S2. Preparation of para-aramid chopped fiber dispersion and meta-aramid fiber precipitation: Adding para-aramid chopped fibers into the nanofiber dispersion to disperse them, and stirring them evenly after a certain period of time to obtain the para-aramid chopped fiber dispersion; The meta-aramid polymer solution, nanofiber dispersion and precipitating agent are continuously and stably added into a precipitation device, and the precipitating device shears the precipitated fibers at high speed into fibrils, and then discharges the precipitated fibers into a water washing tank for further cooling and forming. The cooled and formed fibrillated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, thereby obtaining meta-aramid fibrils with lower crystallinity. S3. Preparation of para-aramid paper: The para-aramid short fiber dispersion and meta-aramid fiber precipitation are subjected to delamination, stirring, wet forming, pressing, drying and hot pressing to obtain the para-aramid paper.

[0023] Specifically, in step S1, the stirring time is 4 to 24 hours, and the storage temperature of the nanofiber dispersion is 15 to 25°C.

[0024] Specifically, in step S1, the weight ratio of para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is (0.05-3): (80-100): (0.01-0.08): (0.15-4).

[0025] Specifically, in step S2, when preparing the para-aramid chopped fiber dispersion, the deflaking time is 5 to 15 minutes; and the mass concentration of the para-aramid chopped fibers in the para-aramid chopped fiber dispersion is 0.05% to 1%.

[0026] Specifically, in step S2, when preparing the meta-aramid fiber, the meta-aramid polymerization liquid has a temperature of 35 to 50° C., a solid content of 8% to 15%, and a viscosity of 100 to 450 Po at 25° C.; When preparing the meta-aramid fiber precipitation, the weight ratio of the nanofiber dispersion liquid, the precipitating agent and the meta-aramid polymer liquid is (5-20): (5-12): (80-100).

[0027] Specifically, in step S2, when preparing the meta-aramid fibrid, the speed of the high-speed shearing is 3500-6000 rpm, and the time of the high-speed shearing is 40-90 s.

[0028] Specifically, in step S2, when preparing the meta-aramid fiber, the precipitating agent is prepared by mixing and compounding the following materials in parts by weight: 5 to 18 parts of chloride salt, 40 to 50 parts of water, and 40 to 50 parts of N,N-dimethylacetamide; The chloride salt is at least one of lithium chloride, calcium chloride and magnesium chloride.

[0029] Specifically, in step S3, the weight ratio of the para-aramid chopped fibers to the meta-aramid fibrids in the para-aramid chopped fiber dispersion is (8-2):(2-8), and the total weight ratio of the para-aramid chopped fiber dispersion and the meta-aramid fibrids is 10 parts.

[0030] Specifically, in step S3, the hot pressing conditions are: temperature 180-220° C., vehicle speed 5-20 m / min, and pressure 100-300 N / mm.

[0031] More specifically, the para-aramid chopped fibers used in the embodiments of the present invention are produced by Taihe New Materials Group Co., Ltd., with a length of 4 to 8 mm and a fineness of 1.5 dtex to 2.0 dtex; the solvents in the meta-aramid polymer solution used in the embodiments of the present invention are all N,N-dimethylacetamide.

[0032] A para-aramid paper is prepared according to the preparation method of the present invention.

[0033] Example 1 Preparation of a para-aramid paper: S1. Preparation of nanofiber dispersion: Para-aramid chopped fibers (1.5 dtex, 5 mm) and potassium hydroxide are added to dimethyl sulfoxide, and then water is added and mechanically stirred for 12 hours to obtain a stable nanofiber dispersion; wherein the weight ratio of para-aramid fibers, dimethyl sulfoxide, water and potassium hydroxide is 2:90:0.05:2; and the storage temperature condition of the nanofiber dispersion is 20°C.

[0034] S2. Preparation of para-aramid chopped fiber dispersion and meta-aramid fiber precipitation: (1) Preparation of para-aramid chopped fiber dispersion: The para-aramid chopped fibers are added into the nanofiber dispersion for decomposition, and after decomposition for 10 minutes, the dispersion is uniformly stirred to obtain the para-aramid chopped fiber dispersion; wherein the mass concentration of the para-aramid chopped fibers in the para-aramid chopped fiber dispersion is 0.6%.

[0035] (2) Preparation of meta-aramid fiber precipitation: The meta-aramid polymer solution, the nanofiber dispersion solution and the precipitating agent are continuously and stably added into the precipitation device, and the precipitated fibers are obtained by high-speed shearing at 5000 rpm for 50 seconds in the precipitation device, and then discharged into a washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; The weight ratio of the nanofiber dispersion, the precipitating agent, and the meta-aramid polymer solution is 15:10:90; The temperature of the meta-aramid polymer solution is 35°C, the solid content is 12%, and the viscosity is 300Po at 25°C; In terms of weight, the precipitating agent is composed of: 10 parts of calcium chloride, 45 parts of water, and 45 parts of N,N-dimethylacetamide.

[0036] S3. Preparation of para-aramid paper: The para-aramid short fiber dispersion and meta-aramid fiber precipitation are subjected to delamination, stirring, wet forming, pressing, drying and hot pressing to obtain the para-aramid paper; The weight ratio of the para-aramid chopped fibers to the meta-aramid fibrils in the para-aramid chopped fibers dispersion is 5:5. The hot pressing conditions were: temperature 200 °C, speed 10 m / min, and pressure 200 N / mm.

[0037] Example 2 Preparation of a para-aramid paper: S1. Preparation of nanofiber dispersion: Para-aramid chopped fibers (1.5 dtex, 5 mm) and potassium hydroxide are added to dimethyl sulfoxide, and then water is added and mechanically stirred for 24 hours to obtain a stable nanofiber dispersion; wherein the weight ratio of para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is 0.05:80:0.01:0.15; and the storage temperature condition of the nanofiber dispersion is 15°C.

[0038] S2. Preparation of para-aramid chopped fiber dispersion and meta-aramid fiber precipitation: (1) Preparation of para-aramid chopped fiber dispersion: The para-aramid chopped fibers are added into the nanofiber dispersion for decomposition, and after decomposition for 5 minutes, the dispersion is uniformly stirred to obtain the para-aramid chopped fiber dispersion; wherein the mass concentration of the para-aramid chopped fibers in the para-aramid chopped fiber dispersion is 0.05%.

[0039] (2) Preparation of meta-aramid fiber precipitation: The meta-aramid polymer solution, nanofiber dispersion and precipitant are continuously and stably added into a precipitation device, and the precipitated fibers are obtained by high-speed shearing at 6000 rpm for 40 seconds in the precipitation device, and then discharged into a washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; The weight ratio of the nanofiber dispersion, the precipitating agent, and the meta-aramid polymer solution is 20:12:100; The temperature of the meta-aramid polymer solution is 40°C, the solid content is 8%, and the viscosity is 100Po at 25°C; In terms of weight, the precipitating agent is composed of 5 parts of lithium chloride, 45 parts of water, and 50 parts of N,N-dimethylacetamide.

[0040] S3. Preparation of para-aramid paper: The para-aramid short fiber dispersion and meta-aramid fiber precipitation are subjected to delamination, stirring, wet forming, pressing, drying and hot pressing to obtain the para-aramid paper; The weight ratio of the para-aramid chopped fibers to the meta-aramid fibrils in the para-aramid chopped fibers dispersion is 2:8; The hot pressing conditions were: temperature 180 °C, speed 5 m / min, and pressure 100 N / mm.

[0041] Example 3 Preparation of a para-aramid paper: S1. Preparation of nanofiber dispersion: Para-aramid chopped fibers (2.0 dtex, 6 mm) and potassium hydroxide are added to dimethyl sulfoxide, and then water is added and mechanically stirred for 4 hours to obtain a stable nanofiber dispersion; wherein the weight ratio of para-aramid fibers, dimethyl sulfoxide, water and potassium hydroxide is 3:100:0.08:4; and the storage temperature condition of the nanofiber dispersion is 25°C.

[0042] S2. Preparation of para-aramid chopped fiber dispersion and meta-aramid fiber precipitation: (1) Preparation of para-aramid chopped fiber dispersion: The para-aramid chopped fibers are added into the nanofiber dispersion for decomposition, and after decomposition for 15 minutes, the dispersion is uniformly stirred to obtain the para-aramid chopped fiber dispersion; wherein the mass concentration of the para-aramid chopped fibers in the para-aramid chopped fiber dispersion is 1%.

[0043] (2) Preparation of meta-aramid fiber precipitation: The meta-aramid polymer solution, nanofiber dispersion and precipitant are continuously and stably added into a precipitation device, and the precipitated fibers are obtained by high-speed shearing at 3500 rpm for 90 seconds in the precipitation device, and then discharged into a washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; The weight ratio of the nanofiber dispersion, the precipitating agent, and the meta-aramid polymer solution is 5:5:80; The temperature of the meta-aramid polymer solution is 50°C, the solid content is 15%, and the viscosity is 450Po at 25°C; In terms of weight, the precipitating agent is composed of: 18 parts of magnesium chloride, 42 parts of water, and 40 parts of N,N-dimethylacetamide.

[0044] S3. Preparation of para-aramid paper: The para-aramid short fiber dispersion and meta-aramid fiber precipitation are subjected to delamination, stirring, wet forming, pressing, drying and hot pressing to obtain the para-aramid paper; The weight ratio of the para-aramid chopped fibers to the meta-aramid fibrils in the para-aramid chopped fiber dispersion is 8:2. The hot pressing conditions were: temperature 220 °C, speed 20 m / min, and pressure 300 N / mm.

[0045] Example 4 Preparation of a para-aramid paper: S1. Preparation of nanofiber dispersion: Para-aramid chopped fibers (1.7 dtex, 6 mm) and potassium hydroxide are added to dimethyl sulfoxide, and then water is added and mechanically stirred for 16 hours to obtain a stable nanofiber dispersion; wherein the weight ratio of para-aramid fibers, dimethyl sulfoxide, water and potassium hydroxide is 1:85:0.03:1; and the storage temperature condition of the nanofiber dispersion is 25°C.

[0046] S2. Preparation of para-aramid chopped fiber dispersion and meta-aramid fiber precipitation: (1) Preparation of para-aramid chopped fiber dispersion: The para-aramid chopped fibers are added into the nanofiber dispersion for decomposition, and after decomposition for 12 minutes, the dispersion is uniformly stirred to obtain the para-aramid chopped fiber dispersion; wherein the mass concentration of the para-aramid chopped fibers in the para-aramid chopped fiber dispersion is 0.2%.

[0047] (2) Preparation of meta-aramid fiber precipitation: The meta-aramid polymer solution, the nanofiber dispersion solution and the precipitating agent are continuously and stably added into the precipitation device, and the precipitated fibers are obtained by high-speed shearing at 5000 rpm for 50 seconds in the precipitation device, and then discharged into a washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; The weight ratio of the nanofiber dispersion, the precipitating agent, and the meta-aramid polymer solution is 10:10:90; The temperature of the meta-aramid polymer solution is 35°C, the solid content is 12%, and the viscosity is 300Po at 25°C; In terms of weight, the precipitating agent is composed of: 15 parts of calcium chloride, 45 parts of water, and 40 parts of N,N-dimethylacetamide.

[0048] S3. Preparation of para-aramid paper: The para-aramid short fiber dispersion and meta-aramid fiber precipitation are subjected to delamination, stirring, wet forming, pressing, drying and hot pressing to obtain the para-aramid paper; The weight ratio of the para-aramid chopped fibers to the meta-aramid fibrils in the para-aramid chopped fibers dispersion is 6:4. The hot pressing conditions were: temperature 200 °C, speed 15 m / min, and pressure 150 N / mm.

[0049] Comparative Example 1 The para-aramid paper was prepared by the same method as in Example 1, except that in step S1, the storage temperature of the nanofiber dispersion was increased. In this comparative example 1, the storage temperature of the nanofiber dispersion was 35°C.

[0050] Comparative Example 2 The para-aramid paper was prepared by the same method as in Example 1, except that in step S1, the storage temperature of the nanofiber dispersion was lowered. In this comparative example 2, the storage temperature of the nanofiber dispersion was 5°C.

[0051] Comparative Example 3 The same method as in Example 1 is adopted to prepare para-aramid paper, except that in step S2, when preparing meta-aramid fibrillation, the dosage ratio of nanofiber dispersion is increased. In this comparative example 3, the weight ratio of nanofiber dispersion, precipitant and meta-aramid polymerization liquid is 25:10:90.

[0052] Comparative Example 4 The same method as in Example 1 is adopted to prepare para-aramid paper, except that in step S2, when preparing meta-aramid fibrillation, the dosage ratio of nanofiber dispersion is reduced. In this comparative example 4, the weight ratio of nanofiber dispersion, precipitant and meta-aramid polymerization liquid is 1:10:90.

[0053] Comparative Example 5 The para-aramid paper was prepared by the same method as in Example 1, except that in step S2, when preparing meta-aramid fibrid, the shear rate was increased. In this comparative example 5, the shear rate of step S2 was 8000 rpm.

[0054] Comparative Example 6 The para-aramid paper was prepared by the same method as in Example 1, except that in step S2, when preparing meta-aramid fibrid, the shear rate was reduced. In this comparative example 6, the shear rate of step S2 was 2000 rpm.

[0055] Comparative Example 7 The conventional method is to coat the nanofiber dispersion on the surface of aramid paper. The specific preparation process is as follows: S1. Preparation of nanofiber dispersion: The nanofiber dispersion was prepared by the same method as in Example 1; S2. Preparation of para-aramid paper: The para-aramid short fibers and meta-aramid fibrils are debonded, stirred, wet-formed, pressed, and dried to obtain the para-aramid base paper; wherein the weight ratio of the para-aramid short fibers to the meta-aramid fibrils is 5:5; S3. Coating of nanofiber dispersion: The nanofiber dispersion prepared in step S1 is uniformly coated on one side of the para-aramid paper prepared in step S2, and then washed and dried, and then the above steps are repeated on the other side of the para-aramid paper to control the total coating amount of the nanofibers on the para-aramid paper to be 2 g / m 2 Finally, the para-aramid paper coated with nanofibers on both sides was hot pressed to obtain the final product. The hot pressing conditions were: temperature 200°C, speed 10m / min, and pressure 200N / mm.

[0056] Comparative Example 8 The para-aramid paper was prepared by the same method as in Example 1, except that the para-aramid chopped fiber dispersion and meta-aramid fibrid were prepared by conventional methods. That is, the nanofiber dispersion was not used in the preparation of the para-aramid chopped fiber dispersion in Comparative Example 8, and the nanofiber liquid was not added in the preparation of the meta-aramid fibrid.

[0057] The specific preparation process of the para-aramid chopped fiber dispersion in Comparative Example 8 is as follows: The para-aramid chopped fibers are added into a proper amount of water for decomposition, and after decomposition for 10 minutes, the para-aramid chopped fibers are uniformly stirred to obtain the para-aramid chopped fibers dispersion; wherein the mass concentration of the para-aramid chopped fibers in the para-aramid chopped fibers dispersion is 0.6%.

[0058] The specific preparation process of the meta-aramid fiber dispersion in Comparative Example 8 is as follows: The meta-aramid polymer solution and the precipitating agent are continuously and stably introduced into the precipitating device, and the precipitated fibers are obtained by high-speed shearing at 5000 rpm for 50 seconds in the precipitating device, and then discharged into a water washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; Wherein, the weight ratio of the precipitating agent to the meta-aramid polymer solution is 10:90; The temperature of the meta-aramid polymer solution is 35°C, the solid content is 12%, and the viscosity is 300Po at 25°C; In terms of weight, the precipitating agent is composed of: 10 parts of calcium chloride, 45 parts of water, and 45 parts of N,N-dimethylacetamide.

[0059] Comparative Example 9 The para-aramid paper was prepared by the same method as in Example 1, except that the para-aramid chopped fiber dispersion was prepared by a conventional method, that is, the nanofiber dispersion was not used when preparing the para-aramid chopped fiber dispersion in this comparative example 9. The specific preparation process of the para-aramid chopped fiber dispersion in this comparative example 9 is as follows: The para-aramid chopped fibers are added into a proper amount of water for decomposition, and after decomposition for 10 minutes, the para-aramid chopped fibers are uniformly stirred to obtain the para-aramid chopped fibers dispersion; wherein the mass concentration of the para-aramid chopped fibers in the para-aramid chopped fibers dispersion is 0.6%.

[0060] Comparative Example 10 The para-aramid paper was prepared by the same method as in Example 1, except that the conventional method was used to prepare the meta-aramid fibrid. That is, no nanofiber dispersion was used in the preparation of the meta-aramid fibrid in this comparative example 10. The specific preparation process of the meta-aramid fibrid in this comparative example 10 is as follows: The meta-aramid polymer solution and the precipitating agent are continuously and stably introduced into the precipitating device, and the precipitated fibers are obtained by high-speed shearing at 5000 rpm for 50 seconds in the precipitating device, and then discharged into a water washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; Wherein, the weight ratio of the precipitating agent to the meta-aramid polymer solution is 10:90; The temperature of the meta-aramid polymer solution is 35°C, the solid content is 12%, and the viscosity is 300Po at 25°C; In terms of weight, the precipitating agent is composed of: 10 parts of calcium chloride, 45 parts of water, and 45 parts of N,N-dimethylacetamide.

[0061] The aramid papers prepared in the above examples and comparative examples were subjected to performance tests, and the test methods involved are specifically as follows.

[0062] The quantitative test method refers to the standard GB / T 451.2; The thickness test method refers to GB / T 451.3; The reference standard for tensile strength and elongation test methods is GB / T 12914; The tear strength test method refers to GB / T 455; The uniformity index is measured by the testing instrument Micro-Scanner; The porosity is measured by a mercury intrusion tester; The specific test results are shown in Tables 1 and 2 below.

[0063] Table 1 Mechanical properties test data of para-aramid paper

[0064] Table 2 Other performance test data of para-aramid paper

[0065] It can be seen from the above table data that the para-aramid paper prepared by the preparation method of the present invention in Examples 1-4 has excellent mechanical properties, good uniformity, low porosity, no glue penetration, and can well avoid the occurrence of glue penetration during the honeycomb preparation process. In Examples 1-4 of the present invention, the para-aramid short fibers are well dispersed in the nano-dispersion liquid, so that the overall performance of the para-aramid paper is significantly improved. At the same time, the aramid nanofibers adhered to the surface of the para-aramid short fibers act as a binder, which not only fills the pores of the aramid paper, but also strengthens the interaction with other fibers. In addition, the introduction of nanofiber dispersion during the preparation of meta-aramid fiber precipitation can moderately reduce its crystallinity, satisfying the balance between energy saving and excellent performance in the processing process. Compared with conventional meta-aramid fiber precipitation, the meta-aramid precipitation surface prepared by the present invention has more tiny wrinkles, which can be more strongly combined with other fibers. At the same time, a strong hydrogen bond force can be formed between the nanofibers and the para-aramid short or meta-aramid fiber precipitation. Under multiple effects, the para-aramid paper of the present invention has excellent overall performance.

[0066] From the data comparison of Comparative Examples 1, 2 and Example 1, it can be seen that if the storage temperature of the nano-dispersion is increased or decreased, the mechanical properties of the para-aramid paper will be significantly reduced. This is because the nano-dispersion at a suitable temperature will disperse the para-aramid chopped fibers more evenly, and the size of the prepared meta-aramid fibrils will be more uniform, and maintain a suitable crystallinity and microscopic morphology (i.e., the surface has more tiny wrinkles). Therefore, the overall performance of the para-aramid paper finally prepared is significantly improved.

[0067] From the data comparison of Comparative Examples 3, 4 and Example 1, it can be seen that if the proportion of the nanofiber dispersion is increased or decreased, the overall performance of the para-aramid paper will also be significantly reduced. This is because by selecting a suitable nanofiber ratio, the prepared meta-aramid fibrils will be more uniform in size and maintain a suitable crystallinity and micromorphology, so that the mechanical properties of the prepared para-aramid paper will be better. At the same time, by selecting a suitable nanofiber ratio, the dispersion state of the para-aramid chopped fibers will reach the best, and the para-aramid paper will be given good overall performance.

[0068] From the data comparison of comparative example 5, comparative example 6 and embodiment 1, it can be seen that maintaining a suitable shearing speed, the overall performance of the para-aramid paper is better. When the shearing rate is too high, the length of the meta-aramid fibrid will be shortened, and the film characteristics of the meta-aramid fibrid will also be reduced, which will cause the contact area of ​​the meta-aramid fibrid and the para-aramid short-cut fiber to be reduced, resulting in the reduction of the mechanical properties and compressive strength of the paper. When the shearing rate is too low, the shearing force received by the aramid droplets is not enough, and the aramid droplets dispersed in the precipitant are larger, and it is impossible to fully stretch into a film state, thereby causing the overall performance of the aramid paper to decrease. In addition, maintaining a certain shearing speed is crucial for the crystallinity of the meta-aramid fibrid. The shearing rate is too high, and the aramid droplets are under the high-speed shearing action, and the fiber is easy to present a film state, and the crystalline structure is destroyed, resulting in a low crystallinity, thereby reducing the fiber strength, and further reducing the mechanical properties of the aramid paper. On the contrary, if the shear rate is too low, the crystallinity of the meta-aramid fibrid is too high, the polymer chain segments are over-aggregated, the gaps are reduced, the flexibility of the molecular chain is reduced, and the mechanical properties of the paper are reduced. The present invention controls the conditions so that the crystallinity of the prepared meta-aramid fibrid is moderately reduced compared with the traditional meta-aramid fibrid, which can not only save energy consumption in the hot pressing process, but also significantly improve the overall performance of the para-aramid paper.

[0069] From the comparison of the data of Comparative Example 7 and Example 1, it can be seen that compared with the method of coating the nanofibers on the surface of the aramid paper, the para-aramid paper in the present invention has better overall performance.

[0070] From the comparison of the data of Comparative Example 8 and Example 1, it can be seen that compared with the conventional method for preparing para-aramid paper, the para-aramid paper prepared by the present invention has significantly improved overall performance.

[0071] From the comparison of the data of Comparative Examples 9 and 10 and Example 1, it can be seen that the aramid paper prepared by using both the meta-aramid fibrid and the para-aramid chopped fiber dispersion of the present invention has better overall performance.

[0072] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0073] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A method for preparing para-aramid paper, characterized in that: The preparation method is: S1. Preparation of nanofiber dispersion: Adding para-aramid chopped fibers and potassium hydroxide into dimethyl sulfoxide, then adding water, stirring and dispersing, to obtain the nanofiber dispersion; S2. Preparation of para-aramid chopped fiber dispersion and meta-aramid fiber precipitation: Adding the para-aramid chopped fibers into the nanofiber dispersion to disperse and mix evenly to obtain the para-aramid chopped fibers dispersion; The meta-aramid polymer solution, nanofiber dispersion solution and precipitating agent are continuously and stably added into the precipitation device, and the precipitated fibers are obtained by high-speed shearing, and then cooled and formed in a washing tank, and multi-stage washing is performed to obtain the meta-aramid precipitated fibers; S3. Preparation of para-aramid paper: The para-aramid short fiber dispersion and meta-aramid fiber precipitation are subjected to delamination, stirring, wet forming, pressing, drying and hot pressing to obtain the para-aramid paper.

2. The method for preparing para-aramid paper according to claim 1, characterized in that: In step S1, the stirring time is 4 to 24 hours, and the storage temperature of the nanofiber dispersion is 15 to 25°C.

3. The method for preparing para-aramid paper according to claim 1, characterized in that: In step S1, the weight ratio of para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is (0.05-3): (80-100): (0.01-0.08): (0.15-4).

4. The method for preparing para-aramid paper according to claim 1, characterized in that: In step S2, when preparing the para-aramid chopped fiber dispersion, the deflaking time is 5 to 15 minutes; and the mass concentration of the para-aramid chopped fibers in the para-aramid chopped fiber dispersion is 0.05% to 1%.

5. The method for preparing para-aramid paper according to claim 1, characterized in that: In step S2, when preparing the meta-aramid fibrid, the meta-aramid polymer solution has a temperature of 35 to 50° C., a solid content of 8% to 15%, and a viscosity of 100 to 450 Po at 25° C.; When preparing the meta-aramid fiber precipitation, the weight ratio of the nanofiber dispersion liquid, the precipitating agent and the meta-aramid polymer liquid is (5-20): (5-12): (80-100).

6. The method for preparing para-aramid paper according to claim 1, characterized in that: In step S2, when preparing the meta-aramid fibrid, the speed of the high-speed shearing is 3500-6000 rpm, and the time of the high-speed shearing is 40-90 s.

7. The method for preparing para-aramid paper according to claim 1, characterized in that: In step S2, when preparing the meta-aramid fiber, the precipitating agent is prepared by mixing the following materials in parts by weight: 5 to 18 parts of chloride salt, 40 to 50 parts of water, and 40 to 50 parts of N,N-dimethylacetamide; The chloride salt is at least one of lithium chloride, calcium chloride and magnesium chloride.

8. The method for preparing para-aramid paper according to claim 1, characterized in that: In step S3, the weight ratio of the para-aramid chopped fibers to the meta-aramid fibrids in the para-aramid chopped fibers dispersion is (8-2):(2-8), and the total weight ratio of the para-aramid chopped fibers and the meta-aramid fibrids in the para-aramid chopped fibers dispersion is 10 parts.

9. The method for preparing para-aramid paper according to claim 1, characterized in that: In step S3, the hot pressing conditions are: temperature 180-220° C., vehicle speed 5-20 m / min, and pressure 100-300 N / mm.

10. A para-aramid paper, characterized in that: The para-aramid paper is prepared according to the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Full-para-polyfiber amide paper, and its preparing method and use

    CN1710196A

  • Preparation process for manufacturing insulated paper by para position fiber and meta position fiber

    CN1884692A

  • Preparation method of PPTA-MPIA in-situ composite fibrid

    CN110184677A

  • Aramid fiber modification method

    CN113389080A

  • Preparation method of heat-conducting aramid insulation paper for high-frequency and high-voltage electrical equipment

    CN114875709A